Avaliação funcional de crianças com comprometimento visual secundário àtoxoplasmose congênita utilizando os instrumentos Avaliação da Visão Funcional (AVIF-2 a 6 anos) e Inventário de Avaliação Pediátrica de Incapacidade (PEDI - versão brasileira) - Aline de Oliveira Brandao (2017)
Introduction: Congenital toxoplasmosis, which is prevalent in Brazil, can damage the retina and visual function, leading to visual impairment. Children with this impairment can benefit from early visual habilitation/development, which aims to minimize delays in neuropsychomotor development. A functional evaluation complements the anatomical information observed by the ophthalmologist and allows planning the appropriate intervention. The tests available for measuring functional performance in this population need further study, withapplicability to different age groups and visual diseases of unique etiologies that could have specific visual deficits. Objectives: The aim of this study is to review the literature on instruments available for evaluating visual function in children with low vision, and to use two of these instruments: Functional Vision Assessment (AVIF-2 to 6 years old) and Pediatric Evaluation of Disability Inventory (PEDI) - to evaluate both visual function and global function, specifically in relation to self-care tasks, in a group of children from Minas Gerais with congenital toxoplasmosis. Method: research was conducted in two stages. The first stage involved a review of the literature regarding tools for evaluating visual function in children with low vision. The Web of Science, Virtual Health Library, Cochrane, Scielo and Pubmed databases were searched for literature published in Portuguese, English and Spanish before September 6, 2016. In the second stage, a cross-sectional study was conducted using data from a group of 96 children with congenital toxoplasmosis who participated in the "EVALUATION OF THE PERCEIVED QUALITY OF LIFE AND VALIDATION OF A TOOL FOR MEASURING QUALITY OF LIFE IN RELATION TO IMPAIRED VISUAL FUNCTION IN CHILDREN WITH CONGENITAL TOXOPLASMOSIS" These children, were eligible to participate in the study because they had no neurological impairment, they had been evaluated by a team of Infant Low Vision specialists, and they had agreed to participate in the research using the two selected instruments to evaluate the childs visual and global functions: AVIF-2 to 6 years old and PEDI, respectively. Excel and Statistical Package for Social Sciences (SPSS) version 20.0 were used to create the database and analyze the statistics. The project was approved by the UFMG Ethics Committee. Results: The function evaluation tools identified in the literature review were mostly aimed at evaluating global functional performance and quality of life, predominantly through the use of questionnaires. Few tools were aimed to preschoolers. Regarding visual function, the AVIF-2 to 6 years old test was noted for its observational format. Two studies used the PEDI interview to evaluate global function in children with low vision, obtaining significant results in relation to mobility and self-care. The cross-sectional study was conducted on the group of 96 children with congenital toxoplasmosis. Most of the children were five years old (85.4%), had retinochoroidal bilateral macular lesions (58.0%) and normal vision (42.7%). Only 16 children were classified as having moderate/severe loss of vision, according to the International Council of Ophthalmology (ICO), 2002. A multiple comparison analysis identified a significant difference in how the children from each group (normal vision, mild loss of vision and moderate/severe loss of vision) performed in the AVIF-2 to 6 years old test, where children with moderate/severe vision loss did not perform as well as the other groups (p <0.0001). The area of the test most affected by the Analysis of Variance was visual tracking (p = 0.022). The PEDI results were not influenced by loss of vision and there was a weak positive correlation (Spearman Correlation) between the two instruments. The results of the AVIF-2 to 6 years old test and the PEDI test were not influenced by the existence of retinochoroidal lesions or their macular location, and when age was examined as a possible confounding factor, no significant difference was found. Only the AVIF-2 to 6 years old instrument was influenced by the visual acuity variable (p = 0.006). Conclusion: Children with moderate/severe vision loss resulting from congenital toxoplasmosis did not perform as well in the use of functional vision according to the AVIF-2 to 6 years old test, especially in relation to visual tracking. This information, together with the morphological findings, will facilitate improved planning of visual development/habilitation processes. The results of the PEDI interview showed no significant global differences in relation to self-care, when the children were grouped according to visual acuity. New studies are needed for evaluating global function in childrenwith visual impairment.